Ferrioxamine Siderophores Detected amongst Iron Binding Ligands Produced during the Remineralization of Marine Particles - Velasquez, Imelda B.; Ibisanmi, Enitan; Maas, Elizabeth W.; Boyd, Philip W.; Nodder, Scott; Sander, Sylvia G. (Frontiers in Marine Science, 2016)
The microbial degradation of marine particles is an important process in the remineralization of nutrients including iron. As part of the GEOTRACES process study (FeCycle II), we conducted incubation experiments with marine particles obtained from 30 and 100 m depth at two stations during austral spring in the subtropical waters east of the North Island of New Zealand. The particles were collected using in-situ pumps, and comprised mainly of suspended and slow sinking populations along with associated attached heterotrophic bacteria. In treatments with live bacteria, increasing concentrations of Fe binding ligands were observed with an average stability constant of logKFeL,Fe3+ = 21.11±0.37 for station 1 and 20.89±0.25 for station 2. The ligand release rates varied between 2.54 and 11.8 pmol L-1 d-1 (calculated for ambient seawater particle concentration) and were similar to those found in two Southern Ocean subsurface studies from ~110 m depths in subpolar and polar waters. Dissolved iron (DFe) was released at a rate between 0.33 and 2.09 pmol Fe L-1 d-1 with a column integrated (30 -100 m) flux of 107 and 58 nmol Fe m-2 day-1 at station 1 and 2, respectively. Given a mixed layer DFe inventory of ~48 µmol m-2 and ~4 µmol m-2 at the time of sampling for station 1 and 2, this will therefore result in a DFe residence time of 1.2 and 0.18 years, assuming particle remineralization was the only source of iron in the mixed layer. The DFe release rates calculated were comparable to those found in the previously mentioned study of Southern Ocean water masses. Fe-binding ligand producing bacteria (CAS positive) abundance was found to increase throughout the duration of the experiment of 7 to 8 days. For the first time ferrioxamine type siderophores, including the well-known ferrioxamine B and G, have been quantified using chemical assays and LC-ESI-MS. Our subtropical study corroborates prior reports from the Southern Ocean of particle remineralization being an important source of DFe and ligands, and adds unprecedented detail by revealing that siderophores are probably an important component of the ligands released into subsurface waters during particle remineralisation.